2023
DOI: 10.1039/d2cc06073f
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal alkaloid with unprecedented triheterocyclic architecture

Abstract: Veratrazine A, a steroidal alkaloid with a unique 6/5/5 triheterocyclic scaffold as the side chain, was isolated from the roots of Veratrum stenophyllum and exhibited moderate and dose-depended anti-inflammatory activities in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…41 Since in Ni[Fe(CN) 6 ] 2 the Ni element is inert in the PBA material and Ni element doping has the ability to activate the low spin Fe activity, Ni element doping can play a role in strengthening the structural stability of the modified material. 42 Ji et al reported a rhombohedral Na-rich nickel hexacyanoferrate (r-NiHCF) that possesses long cycling stability, and the excellent stability of r-NiHCF can be assigned to the absence of rhombohedral-cubic phase transition and negligible volume variation during electrochemical redox reac-tions. 43 On the other hand, a self-healing strategy of selfhealing materials has been proposed to solve the problem of poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…41 Since in Ni[Fe(CN) 6 ] 2 the Ni element is inert in the PBA material and Ni element doping has the ability to activate the low spin Fe activity, Ni element doping can play a role in strengthening the structural stability of the modified material. 42 Ji et al reported a rhombohedral Na-rich nickel hexacyanoferrate (r-NiHCF) that possesses long cycling stability, and the excellent stability of r-NiHCF can be assigned to the absence of rhombohedral-cubic phase transition and negligible volume variation during electrochemical redox reac-tions. 43 On the other hand, a self-healing strategy of selfhealing materials has been proposed to solve the problem of poor stability.…”
Section: Introductionmentioning
confidence: 99%